If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 12y = 4 Solving 6x + 12y = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12y' to each side of the equation. 6x + 12y + -12y = 4 + -12y Combine like terms: 12y + -12y = 0 6x + 0 = 4 + -12y 6x = 4 + -12y Divide each side by '6'. x = 0.6666666667 + -2y Simplifying x = 0.6666666667 + -2y
| k+4+l=18 | | 5(4z)-1/2z=234 | | 9x=8x+96 | | 3/3/10 | | 3/5n=21 | | 10s-5+3=9s+2 | | 3+2x-1x-1=3x-6 | | 50h+75=65 | | 2.5x=.5x+150 | | -x/8+3=9 | | -13=r-17 | | 37-c=23 | | 12x^4-13x^2+5=0 | | ax^2+2x+4=0 | | 18+-128= | | 3/4-r=-1/3 | | 13x^4+9x^2+2=0 | | 8nr^6h+8nr^9= | | 12b^3-8b=0 | | 10s-5+3=3(3s+2) | | y=0.2x^2-7 | | A=k+ab+5b-3b | | 6(.75)-10=2(.75)-7 | | 64+-1= | | 15ab-35ab^2= | | k=ab+5b-3b | | 5/2c=8/1/3 | | -40=6-6s | | 4x*2x=y | | 7-2j+8J-3= | | k=ab+5b-3b(fora) | | -5+18-24= |